Political ideology, groupness, and attitudes toward Marijuana legalization - Ramos, Guilherme de Alencar (2018)
Prior literature has demonstrated that liberals and conservatives often diverge on policy issues partly because they have different psychological characteristics and partly because they are influenced by in- and out-groups (e.g., parties). In the present work, we investigate a relatively under-investigated topic, namely marijuana legalization, and test whether groupness affect opinion toward this policy over and above potential differences in psychological traits and states (e.g., personality, cognitive processing). Additionally, building on literature on morality and divergence from reference groups, we propose that part of the right-wing’s opposition to this policy comes from moral repugnance against out-groups. Results are consistent with our predictions. Study 1 validated an important assumption: individuals strongly associate marijuana legalization as a leftist policy. Importantly, study 2 showed that when marijuana legalization was endorsed by a center-right politician, individuals along the political spectrum expressed similar support for the policy; nevertheless, political ideology became a significant predictor of policy support when a leftist politician was behind the policy. This interaction was mostly due to rightwing individuals becoming less favorable toward the policy when a left-wing politician was behind it. Left-wing individuals, in turn, did not significantly shift their opinion. Finally, we discuss limitations, alternative explanations, and avenues for future research, while also proposing a third study which could more precisely test our theory.